Corporate Social Responsibility, Corporate Governance, dan Corporate Risk Disclouser terhadap Nilai Perusahaan - kesumadewi, dara; Rahma Gita Suci; Annie Mustika Putri (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
This study aims to examine the effect of corporate social responsibility, independent commissioners, institutional ownership, audit committees, and corporate risk disclosure on firm value in basic materials sector companies listed on the Indonesia Stock Exchange during the period 2021–2023. The data used in this study were obtained from companies’ annual reports accessed through www.idx.co.id. The population of this study consists of all basic materials sector companies listed on the Indonesia Stock Exchange, totaling 112 companies. The sampling technique employed was purposive sampling, resulting in 20 companies that met the predetermined criteria over three years of observation, yielding a total of 60 observations. The data were analyzed using multiple linear regression with the assistance of IBM SPSS 26. The results indicate that corporate social responsibility, institutional ownership, and corporate risk disclosure have a significant effect on firm value in basic materials sector companies listed on the Indonesia Stock Exchange. Meanwhile, independent commissioners and audit committees do not have a significant effect on firm value in basic materials sector companies listed on the Indonesia Stock Exchange.